The viscosity and processing of molten lunar regolith - James Bowen; Vibha Levin Prabhu; Sungwoo Lim; Mahesh Anand (Scientific Reports)
Abstract Establishing a permanent, self-sufficient habitat for humans on planetary bodies is critical for successful space exploration. In-situ resource utilisation (ISRU) of locally available resources offers the possibility of an energy-efficient and cost-effective approach. This paper considers the high-temperature processing of molten lunar regolith under conditions which represent the lunar environment, namely low gravity, low temperature, and negligible atmospheric pressure. The rheological properties of the low-titanium lunar mare regolith simulant JSC-1A are measured using concentric cylinder rheometry and these results are used to explore the influence of viscosity on processing operations involving the flow of molten regolith for fabricating construction components on the Moon surface. These include the delivery of molten regolith within an extrusion-based 3D printing technique and the ingress of molten regolith into porous structures. The energy and power required to establish and maintain sufficiently high temperatures for the regolith to remain in the liquid state are also considered and discussed in the context of lunar construction.